Development of a laser chipping technique combined with water jet for retrieval of fuel debris at Fukushima Daiichi Nuclear Power Station. Issue 12 (2nd December 2019) - Yamada, Tomonori; Takebe, Toshihiko; Ishizuka, Ippei; Daido, Hiroyuki; Hanari, Toshihide; Shibata, Takuya; Ohmori, Shinya; Kurosawa, Koichi; Sasaki, Go; Nakada, Masahiro; Sakai, Hideaki
ABSTRACT: We describe a new chipping technique combined with a water-jet technique as one of the candidate techniques for the retrieval of fuel debris and support structures as part of the decommissioning of the Fukushima Daiichi Nuclear Power Station (1F). We performed proof-of-principle experiments to demonstrate the removal capability of metal parts, where we focused on the observation of removal processes from a metallic sample using a 5.5-kW continuous wave fiber laser combined with continuous and pulsed water jets. We observed the dynamic behavior of our new technique using a high-speed camera. From the experiment results, the repetitive pulsed water jet was advantageous over the continuous one in the efficient removal of molten parts of the metal sample under our experiment conditions. The results revealed that excessive cooling in the laser irradiation area prevented efficient the removal of molten metal. With addition of the pulsed water jet, the laser chipping technique for volumetric removal of the metal sample was successfully demonstrated. The removal rate of stainless steel was 60–80 g/min, which could increase with increasing laser power coupled with an optimized water jet shooting condition. Finally, we provide a phenomenological description of the present results and we also discuss the prospective applications.